1996
DOI: 10.1073/pnas.93.19.10280
|View full text |Cite
|
Sign up to set email alerts
|

Plant virus DNA replication processes in Agrobacterium: insight into the origins of geminiviruses?

Abstract: Agrobacterium tumefaciens, a bacterial plant pathogen, when transformed with plasmid constructs containing greater than unit length DNA of tomato leaf curl geminivirus accumulates viral replicative form DNAs indistinguishable from those produced in infected plants. The accumulation of the viral DNA species depends on the presence of two origins of replication in the DNA constructs and is drastically reduced by introducing mutations into the viral replication-associated protein (Rep or Cl) ORF, indicating that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
41
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 25 publications
4
41
1
Order By: Relevance
“…It has been suggested that geminiviruses have evolved from prokaryotic circular ssDNA replicons (9,12). If this scenario is correct, one would expect to observe geminiviruses in different eukaryotic kingdoms.…”
Section: Replication Initiator Motifs In Helitronsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been suggested that geminiviruses have evolved from prokaryotic circular ssDNA replicons (9,12). If this scenario is correct, one would expect to observe geminiviruses in different eukaryotic kingdoms.…”
Section: Replication Initiator Motifs In Helitronsmentioning
confidence: 99%
“…They encode only one protein, similar to the replication initiator proteins (Rep) from known RC replicons (6)(7)(8)(9). There are three groups of episomal replicons using RCR: circular single-stranded DNA (ssDNA) bacteriophages (10), plasmids of bacteria or archaea (11), and geminiviruses (circular ssDNA viruses replicating in plant cells) (12). Usually replication of RC replicons is catalyzed by the nuclease͞ligase activity of Rep and is assisted by host DNA helicases and ssDNA-binding proteins (SSBs) (6)(7)(8)(9)(10)(11)(12).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Rather than by cut and paste, these DNA elements are proposed to move through replication and strand replacement. This mode of propagation, called rolling circle transposition, has been reported previously in some insertional sequence groups of transposable elements in prokaryotes (Tavakoli et al, 2000), bacterial plasmids (Khan, 2000), and the circular single-stranded DNA of plant geminiviruses (Rigden et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…These results suggested that induction of SlNAC1 in response to TLCV infection is mediated by REn, and also demonstrated that SlNAC1 is not induced nonspecifically in response to A. tumefaciens infection or wounding associated with the infiltration procedure. In a subsequent experiment, a TLCV derivative containing a mutation in the C3 gene that prevents translation of the REn protein (Rigden et al, 1996) was tested for its effect on SlNAC1 expression. The level of SlNAC1 transcript in tomato plants agroinoculated with the REn mutant was comparable to healthy controls 25 dpi ( Figure 7D, top).…”
Section: Tlcv Infection Induces the Expression Of Slnac1mentioning
confidence: 99%